Intramedullary Subependymoma of the Cervical Spinal Cord: A Case Report and Review of the Literature - Eiralí Guadalupe García Chapa; Juana Elizabeth Tadeo González; Mauricio Delgado Morquecho; José Armando Díaz Martínez; Mariana Mercado Flores; Ángel Martínez Ponce De León; Oralia Barboza Quintana; Rodolfo Franco Márquez (Indian Journal of Neurosurgery)
Subependymoma is a rare tumor of the central nervous system, representing 0.2 to 0.7% of all intracranial tumors. They are usually found in the fourth ventricle or in the walls of the lateral ventricles, often remaining asymptomatic. Subependymomas occur rarely in the cervical or thoracic spinal cord. Since its first description in the spinal cord by Boykin et al in 1954, only 47 cases have been reported. A 49-year-old man presented with a 4-year-long-lasting neck pain, which radiated to the upper right extremity for 4 years. It was insidious at onset and revealed gradual progression, difficulty in performing fine hand movements, and hyperalgesia. Magnetic resonance imaging revealed irregular hyperintensity of T2 and dilatation of the spinal cord from C4 to T1 with associated edema and an intramedullary lesion with central location. During the surgical event, a transoperative biopsy was performed that revealed loose fibrillary networks and groups of nuclei showing mild pleomorphism and microcystic formations. Histologically, we observed groups of cells with mild nuclear pleomorphism embedded in a dense, thin, glial fibrillar fundus, and microcystic formations. Immunohistochemical staining revealed diffuse positivity for the glial fibrillary acidic protein, and negative for the epithelial membrane antigen. Subependymoma accounts for 8.3% of all ependymal tumors. There are few descriptions of the cytologic features of the subependymoma because this neoplasm is rare and most commonly found incidentally in autopsies.